The E–Id protein axis modulates the activities of the PI3K–AKT–mTORC1–Hif1a and c-myc/p19Arf pathways to suppress innate variant T(FH) cell development, thymocyte expansion, and lymphomagenesis - Miyazaki, Masaki (Genes Dev, 2015)
It is now well established that the E and Id protein axis regulates multiple steps in lymphocyte development. However, it remains unknown how E and Id proteins mechanistically enforce and maintain the naïve T-cell fate. Here we show that Id2 and Id3 suppressed the development and expansion of innate variant follicular helper T (T(FH)) cells. Innate variant T(FH) cells required major histocompatibility complex (MHC) class I-like signaling and were associated with germinal center B cells. We found that Id2 and Id3 induced Foxo1 and Foxp1 expression to antagonize the activation of a T(FH) transcription signature. We show that Id2 and Id3 acted upstream of the Hif1a/Foxo/AKT/mTORC1 pathway as well as the c-myc/p19Arf module to control cellular expansion. We found that mice depleted for Id2 and Id3 expression developed colitis and αβ T-cell lymphomas. Lymphomas depleted for Id2 and Id3 expression displayed elevated levels of c-myc, whereas p19Arf abundance declined. Transcription signatures of Id2- and Id3-depleted lymphomas revealed similarities to genetic deficiencies associated with Burkitt lymphoma. We propose that, in response to antigen receptor and/or cytokine signaling, the E–Id protein axis modulates the activities of the PI3K–AKT–mTORC1–Hif1a and c-myc/p19Arf pathways to control cellular expansion and homeostatic proliferation.